Rheological behavior and stability of cassava starch for ceramic mould binder application - Alias, Tuti Yasmin; Idris, Mohd Hasbullah; Ahmad, Zuraida; Ourdjini, Ali (Trans Tech Publications, Switzerland, 2012)
Silica free binder was developed from cassava starch to correspond common ceramic mould binder for reactive metal casting application. Ceramic slurry rheology behavior and stability depends on both binder and refractory materials properties. Starch processing started from granule expansion or swelling, gelatinization, depolymerization via prolong heating and by adding plasticizer, citric acid is to improve viscosity. Pseudoplastic or shear thinning behavior for both binder and slurry were observed starting at 0.13 Pa.s and 2.5 Pa.s respectively. Calcium carbonate (aragonite) slurry from starch binder however, exhibited viscoelastic behavior compare to colloidal silica sol. Ceramic slurry aged as both cationic starch and CaCO3 flocculate and not exfoliate as indicated by increased in the pH of the slurry.